2006
DOI: 10.1091/mbc.e05-11-1056
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of theDrosophilaZinc Finger-encoding GenevielfältigImpair Mitotic Cell Divisions and Cause Improper Chromosome Segregation

Abstract: We describe the molecular characterization and function of vielfä ltig (vfl ), a X-chromosomal gene that encodes a nuclear protein with six Krü ppel-like C2H2 zinc finger motifs. vfl transcripts are maternally contributed and ubiquitously distributed in eggs and preblastoderm embryos, excluding the germline precursor cells. Zygotically, vfl is expressed strongly in the developing nervous system, the brain, and in other mitotically active tissues. Vfl protein shows dynamic subcellular patterns during the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
102
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(122 citation statements)
references
References 45 publications
16
102
2
2
Order By: Relevance
“…For the C2H2 TF STZ, where mutants have enhanced tolerance to salt and abiotic stresses, we also saw enrichment in mitosis-related functions (Figure 4, box 4). As C2H2 family members from both plants and animals are known to regulate the cell cycle and DNA replication (Staudt et al, 2006;Welch et al, 2007), STZ enrichment for mitotic functions suggests that its stress response phenotype may involve direct regulation of cell division. Finally, bHLH122, known to be important for abiotic drought responses, targeted genes in immune processes (Figure 4, box 3), suggesting that it may also play a role in biotic defense.…”
Section: The Arabidopsis Cistromementioning
confidence: 99%
“…For the C2H2 TF STZ, where mutants have enhanced tolerance to salt and abiotic stresses, we also saw enrichment in mitosis-related functions (Figure 4, box 4). As C2H2 family members from both plants and animals are known to regulate the cell cycle and DNA replication (Staudt et al, 2006;Welch et al, 2007), STZ enrichment for mitotic functions suggests that its stress response phenotype may involve direct regulation of cell division. Finally, bHLH122, known to be important for abiotic drought responses, targeted genes in immune processes (Figure 4, box 3), suggesting that it may also play a role in biotic defense.…”
Section: The Arabidopsis Cistromementioning
confidence: 99%
“…Depletion of zygotically transcribed Vielfaltig results in chromosome segregation and DNA replication defects (Staudt et al 2006), leading us to hypothesize that TAGteam motifs might play a role in ORC positioning. Using published ORC ChIPseq data from mixed-stage embryos (Roy et al 2010), we confirmed previous reports (MacAlpine et al 2010) of a strong correlation between chromatin accessibility and ORC binding.…”
Section: Binding Of the Origin Recognition Complex Is Anticorrelated mentioning
confidence: 99%
“…Vielfaltig has six C2H2 zinc fingers, two N-terminal and four C-terminal (Staudt et al 2006), of which the C-terminal zinc fingers are sufficient to recapitulate its known DNA-binding specificity (Liang et al 2008). Vielfaltig may help to maintain chromatin in an accessible state, participate in permissive protein-protein interactions, or have particular interaction partners.…”
Section: Org Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…1A) (3,10). There are no other identifiable protein domains that might suggest an enzymatic activity.…”
mentioning
confidence: 99%